Pérdida de fuerza ejecutoria de los actos administrativos en Colombia (2018)
The public administration has been forced to obtain the material fulfillment of the decisions making at the end of an administrative procedure. For this purpose the legislator has provided a period of five years, to wholly comply with the decision. Nevertheless an administrative act loses its enforceability, when one of this attributes disappears, and consequently loses capacity to produce legal effects. As provided under the Article 91 of the Law 1437 of 2011, lays down the cases in which administrative acts will not be mandatory, and therefore will lose enforceability. Thus, the third cause is being the subject of the current investigation, of which it may be noted that the administration does not carry out all the necessary action to fulfil this objective , which might be due to some variables analyzed for development of the present proposal, to the excessive workload, which result in unbearable congestion, and in another sense to the lack of rigor in the attention to plans and objectives that the administration has drawn what becomes in an inefficient management of activities within the expected term